The Influence of Leadership, School Culture, and Self-Efficacy on the Performance of Public Junior High School Teachers in Kuala Kampar Sub-District, Pelalawan Regency - Eva Yulianti; Wiwik Wijayanti; Josefa Flores (Yayasan Adra Karima Hubbi, 2025)
Background. This study aims to analyze the influence of leadership, school culture, and self-efficacy on teacher performance, both partially and simultaneously. Specifically, this study examines how leadership affects teacher performance in carrying out their duties, the extent to which school culture contributes to creating a work environment that supports performance improvement, and the role of self-efficacy in building teacher confidence and professionalism. Purpose. This study aims to analyze the influence of leadership, school culture, and self-efficacy on teacher performance, both partially and simultaneously. Method. This study used a quantitative approach with an ex-post facto method. The population in this study were 78 teachers of SMP Negeri Kuala Kampar District, with a sample size of 78 people selected using purposive sampling technique. Data collection was done through distributing questionnaires, which were then analyzed using multiple linear regression, partial test (t test), simultaneous test (F test), and the coefficient of determination (R²). Results. The results showed that leadership has a positive and significant influence on teacher performance with a significance value of 0.000 (<0.05). School culture also has a positive and significant effect on teacher performance with a significance value of 0.000 (<0.05). Similarly, self-efficacy has a positive and significant effect on teacher performance with a significance value of 0.000 (<0.05). Simultaneously, leadership, school culture, and self-efficacy have a significant influence on teacher performance with a significance value of 0.000 (<0.05). Conclusion. These findings suggest that effective principal leadership can create a conducive work environment and increase teacher motivation, while a positive school culture supports teachers' professionalism and commitment in carrying out their duties. In addition, high self-efficacy encourages teachers to be more confident in managing learning. Therefore, a holistic approach that includes adaptive leadership, inclusive school culture, and strengthening teachers' self-efficacy is needed to improve the quality of education.